Captopril and Valsartan May Improve Cogniti ve Function Through Potentiation of the Brain Antioxidant Defense System and Attenuation of Oxidative/Nitrosative Damage in STZ - Induced Dementia in Rat - Yasaman Arjmand Abbassi; Mohammad Taghi Mohammadi; Mahsa Sar ami Foroshani; Javad Raouf Sarshoori (Tabriz University of Medical Sciences, 2016)
Purpose: Previous findings have shown the crucial roles of brain renin-angiotensin system (RAS) in pathogenesis of Alzheimer's disease (AD). Since RAS inhibitors may have beneficial effects on dementia and cognitive function in elderly people, the aim of present study was to examine the neuroprotective actions of captopril and valsartan on memory function and neuronal damage in experimental model of AD. Methods: Adult forty male Wistar rats (220-280g) were randomly divided into 5 groups; Control, Vehicle, Alzheimer and treatment groups. AD was induced by the injections of streptozotocin (3mg/kg, bilateral intracerebroventricular) at days 1&3. Treated rats received orally captopril (50mg/kg/day) and valsartan (30mg/kg/day). Memory function and histological assessments were done at termination of experiment. Finally, superoxide dismutase (SOD) and catalase (CAT) activities as well as malondialdehyde (MDA) and NOx contents were determined. Results: There was a significant increase in the mean value of latency in Alzheimer group (66%). Captopril and valsartan considerably decreased this value in both treatment groups (45% and 72%, respectively). In Alzheimer group the activities of brain's SOD and CAT reduced (40% and 47%, respectively) in accompany with an increase in MDA and NOx contents (49% and 50%, respectively). Captopril and valsartan significantly increased the activities of brain's SOD and CAT concomitant reduction in MDA and NOx contents. Also, histopathological damages noticeably decreased in both treatment groups. Conclusion: Our findings indicate that RAS inhibition by using captopril and valsartan potentiates the antioxidant defense system of brain and reduces oxidative/nitrosative stress in accompany with neuronal damage during AD.